Building knowledge: using didactic models in cytology in the pandemic (Research, Society and Development, 2022)
The teaching of cytology is complex for students to understand, as it is abstract, Within this context, the use of didactic models are tools that collaborate with the teacher to make the content more concrete. In order to propose a systematization of this abstraction, it was proposed to the students of the physical education course, the realization of cell models and that could concurrently with didactic facilitation, allow the teacher means to measure the learning process. The experience report sought to verify whether there was an understanding of the cellular functions, after the construction of the models, of an animal eukaryotic cell, and whether this methodology contributes to reduce the abstraction in relation to the content. It was possible to perceive through the students' reports that the methodology was positive, made possible the association between cellular organelles and their functions, favoring understanding and learning.